Design, Fabrication, and Comparative Study of Electronically Tunable Active Filters. (1995) - Kumar, Umesh; Mital, P. Bhushan
Abstract : The Kerwin-Huelsman Newcomb (KHN) biquad is the natural choice for use as a 'universal' filter building block out of the several existing 3-amplifier biquadratic filter sections based on the two integrator loop or state variable realization of 2nd order systems. A modified version of the KHN biquad, which is electronically tunable almost linearly over a decade range of center frequency, is presented. For electronic tunability, instead of the direct use of a FET as a voltage variable resistance to control the time constants of the integrators, a novel approach of using voltage-controlled variable-gain amplifiers at the inputs of both the integrators and one immediately after the input signal has been suggested. The circuit is suitable for use as a tunable universal filtering module and can be easily digitally programmed. Comparative treatment of general tuning methods of active filters, and some methods of electronic tuning of active filters are discussed. A brief description of tuning algorithms of active filters is also given.